The element of gambling in conventional insurance and takaful - Hashim, Suraiya; Shahidan, Asnida; Fadzim, Wan Roshidah (Jabatan Ekonomi Awam & Kewangan, Fakulti Ekonomi, Universiti Utara Malaysia, 2005)
Conventional insurance is said to contain the prohibitive elements of usury (al-riba), uncertainty (al-gharar) and gambling (al-maisir). However, the central idea of insuring a party against pure risk does not contradict the Islamic spirit. The Islamic model of insurance or takaful is supposedly to run without the usury, ambiguities and gambling elements. Some scholars, however are still questioning the Shari'ah legitimacy of Islamic insurance in view of the gambling (al-maisir) features found in the takaful operations. This study seeks to identify the gambling (al-maisir) element in the insurance and takaful. Four listed characteristics of gambling given in the study was found in conventional insurance. It can be concluded that conventional insurance resembles gambling, if not identical to it. However, it was found that conventional insurance has less resemblance to takaful because the listed characteristics of gambling was not found in takaful operation. This indicates that takaful business does not resemble gambling since it (i.e. takaful) has no resemblance to conventional insurance.